Individual minority shareholder activism and directors’ response in listed corporations in Malaysia - Othman, Sarina (2018)
Recent developments associated with corporate governance and shareholder activism have shown that shareholder empowerment is vital. Hence, there is a dire need for minority shareholders to be more active and responsive in their dealings and communications with corporations. Surprisingly individual minority shareholder activism has received less attention than institutional shareholders, not only in practice but also in the academic world. Additionally, firm response towards such activism efforts remains poorly explored. This study has taken the form of a two-level analysis which incorporates individual minority shareholders and the board of directors (an agent) as the informants for data collection purposes. Therefore, this study broadly seeks an understanding of individual minority shareholder activism in the context of Malaysia via analysis of the various approaches adopted, the level of engagement, the drivers for such engagement, the challenges faced to effectively engage with the company and the roles of Minority Shareholder Watchdog Group (MSWG) in facilitating shareholder activism. This study also seeks to understand how boards of directors perceive individual minority shareholder activism, and discover how activism is actually responded to and handled at the company level. From the methodological perspective, this study is regarded as a qualitative type of research. From the interpretivist point of view, semi-structured interviews with 24 participants— the individual shareholders (15) and the directors (9) was carried out. Face-to-face semi-structured interviews were utilized to obtain the primary data for this study. Data from the interviews were carefully transcribed and analysed using a thematic analysis approach. From the findings, it was discovered that individual minority shareholders were neither all passive nor all active. Some viewed themselves as moderately engaged, due to the lesser impact brought by their engagement. Most shareholders were still very much engaged with the companies in activities related to Annual General Meetings (AGMs), with some emerging platforms, such as the social media and forming an activist group to collectively engage with the company. In fact, voice mechanism was favoured by these shareholders to engage, and they considered this approach can significantly be heard. When individual shareholders engaged with the company, it was discovered that they were still driven by the financial motives with several emerging drivers. Notwithstanding this engagement, several broad categories of challenges were identified, with individual challenges related to the most challenging settings of individual shareholder activism. It was also revealed that despite recognition given to the roles and the importance of MSWG in the activism process, these shareholders had never really exploited MSWG. At the director level, it was found that the directors had warmly welcomed such activism. Reasons given in responding to such activism include ensuring a good relationship with the shareholders, espousing transparency, and maintaining corporate image and reputation. In responding to individual minority shareholders, it was found that Malaysian listed companies have each adopted different methods to deal with the activism issues raised. This study has made several contributions. Theoretically, this study injected the communication elements to shareholder activism and utilization of Exit, Voice, Loyal, Neglect (EVLN) model enriches the categorization of activism approaches of individual minority shareholders in Malaysia. In practice, this study strengthens the effort for more active engagements by individual minority shareholders in the companies such as the proposal to provide specific procedure or officials to response to such activism. The finding of the study also suggested MSWG to continue to educate the individual minority shareholders to professionally engage with the companies.